Effect of crop establishment methods and irrigation schedules on economics of wheat (Triticum aestivum) production, moisture depletion pattern, consumptive use and crop water-use efficiency - MAURYA, R K; SINGH, G R (The Indian Journal of Agricultural Sciences, 2011)
A field experiment was conducted during winter (rabi) season of 2003–04 and 2004–05 at Kumarganj, Uttar Pradesh to study the effect of crop establishment method and irrigation schedule on water parameters and economics of wheat (Triticum aestivum L. emend. Fiori & Paol.) production. Highest net returns (Rs 14 965/ha) and net returns/rupee invested (Rs 1.03) were recorded under rota till drill against minimum value recorded under conventional (drill) method of crop establishment. The highest consumptive use (32.79 and 28.51 cm) was recorded under conventional (drill) method of crop establishment. While, water-use efficiency (131.38 and 173.88 kg/ha-cm) was highest under the bed planting. The highest consumptive use (33.91 and 28.49 cm) was recorded with 6 cm irrigation at 1.2 IW: CPE.